Prevalence of good glycaemic control and its associated factors among gestational diabetes patients in Bachok, Kelantan - Rasmi, Muhammad Faiz (2017)
Introduction: The prevalence of GDM has shown an increasing trend from year to year. GDM can be effectively controlled and uncontrolled GDM had been associated with a wide range of morbidities and mortalities to mothers and infants. Hence, it is important to ensure that mothers with GDM have good glycaemic control in order to prevent these negative outcomes. Objectives: To determine the prevalence of good glycaemic control and its associated factors among GDM patients attending antenatal clinic in Bachok. Methodology: This is a cross sectional study with retrospective record review of 129 GDM patients who were diagnosed from June to November 2014 The sociodemographic and medical characteristics of patients were gathered from the antenatal cards and recorded in the case report form. The medical characteristics of interest includes BMI at booking, gestational age when GDM was diagnosed, weight gain until GDM was diagnosed, level of FBG and 2HPP at diagnosis, abortion history, previous history of GDM and history of macrosomic baby. Good Glycaemic Control was defined as either: (i) having at least 75% of the blood sugar profile (BSP) readings within the normal range in two consecutive BSP readings or (ii) those who do not require insulin after two consecutive blood sugar profile (BSP) readings. Data was entered and analysed using SPSS version 22.0.Results: The prevalence of good glycaemic control was 61.2% (95% CI, 0.53, 0.70) (n =79). The mean (SD) age and parity (SD) of patients in this study were 31.2(6.00) and 3.4(2.08) respectively. Multiple logistic regression showed that gestational age at GDM diagnosis (OR= 0.93, 95% CI: 0.87, 1.00, p= 0.048), level of FBG at GDM diagnosis (OR= 0.28, 95% CI: 0.15, 0.50, p= 0.001), previous history of GDM (OR= 0.23, 95% CI: 0.06, 0.84 p= 0.026) and history of macrosomic baby (OR= 10.45, 95% CI: 1.80, 60.69 p= 0.009) were significantly associated with good glycaemic control. Conclusion: The prevalence of good glycaemic control among GDM patients in this study was acceptable. Gestational age at GDM diagnosis, level of FBG at GDM diagnosis, presence of previous GDM history and no history of macrosomic baby were associated with good glycaemic control of GDM.